Pembiasaan Menggunakan Jilbab pada Anak Usia Dini dalam Rangka Mengenalkan Pendidikan Agama Moral - Aeni Latifah; Lia Trinuari Wahyuni; Sarmita Sarmita; Tiara Dina Cahyani (Institut Madani Nusantara, 2024)
Early childhood refers to children aged 0–6 years, a vulnerable and golden age for children. Children are born with their own potential, and their character needs to be shaped to support their future. Education can help maximize both, particularly religious education. Religious education is crucial and serves as the foundation for life between this world and the hereafter. It also balances children's knowledge. Religious education can be incorporated into children's daily routines. One strategy is to introduce the hijab to girls as a symbol of Muslim identity, which not only serves to cover their genitals but also contains religious values, obedience, and the formation of noble morals. The purpose of this study was to determine the habit of wearing the hijab among early childhood children in order to introduce moral religious education. This study used a descriptive qualitative method and was conducted at Pembina Cibeureum State Kindergarten. The subjects included group A early childhood children aged 5 years and 3 months, teachers, and parents. Data were obtained through observation, interviews, and documentation. The research results show that habituating children to wearing the hijab has a positive impact on shaping their religious awareness and Islamic identity. Therefore, encouraging children to wear the hijab without parental coercion can be an effective strategy for integrating religious and moral education from an early age.